P-469 Micro-vapor fast freezing of human spermatozoa: development of a new method to use low number of cryopreserved spermatozoa. (30th June 2022) - Dabizzi, S; Muratori, M; Degl'Innocenti, S; Vignozzi, L; Maggi, M
Abstract: Study question: Can Vapor Fast Freezing conducted in 10µl tips (microVFF/tips) efficiently preserve sperm viability and motility in banking samples with very low sperm concentration? Summary answer: MicroVFF resulted able to efficiently preserve sperm viability and motility in patients with severe oligozoospermia or criptozoospermia What is known already: Sperm cryopreservation is usually performed by conventional slow or fast freezing using carriers containing large semen volume, such as 500ul High Security Straws (500µl HSS). These carriers however are not suitable for patients with very low sperm concentration and many devices have been tested to freeze small volumes or even singularly isolated sperms (i.e.SpermVD®, Cryoloop, Cell Sleeper). Recently, our group showed that micro-VFF better preserve sperm viability and motility or DNA integrity with respect to a VFF conducted with 500µl HSS, in normozoospermic samples. Study design, size, duration: The study was designed for 20 oligospermic or criptozoospermic subjects afferent to Semen Cryopreservation and Andrology Laboratory of Careggi Hospital for semen analysis, but during 24 months up to 34 patients were recruited for the trial. 13 samples were subsequently thawed and, due to the low sperm number, only motility and viability was compared between the two methods. Participants/materials, setting, methods: 34 semen samples with low sperm concentration (0.06-7.7mil/ml) were cryopreserved with either microVFF/tips or the conventional method (VFF/ 500µl HSS). Thawing was conducted by keeping sample at room temparature and immediately observed by light microscopy at 20x and 40x. Total motility was scored as rapid/slow/non-progressive motility (a+b+c). Viability was evaluated by eosin test. For each method, the recovery of motility and viability was calculated as: post-thaw percentage/pre-thaw percentage Main results and the role of chance: The microVFF method showed a better recovery of motility than the conventional method: 0.38 (±0.21)% vs 0.21 (±0.14)% (n = 13, p < 0.05). A similar statistically significant difference was observed for the mean recovery of viability: 0.43 (±0.20) vs 0.29 (±0.13) (n = 13, p < 0.5). for micro-freezing and conventional method, respectively. As frozen samples are used in the ART setting, microVFF/tips also shows the technical advantage to discharge directly the sample in fresh clean medium bridge in the ICSI plate, where swimming spermatozoa are washed from cryoprotectant compounds. Skipping conventional centrifugation/washing step after thawing highly protect from sperm motility/viability loss, as recently demonstrated by our group. Limitations, reasons for caution: Results need to be confirmed in a larger number of patients. Although we previously showed that microVFF/tips also better preserve sperm DNA integrity than conventional method, in this study no other evaluations were possible due to the low number of spermatozoa/sample Wider implications of the findings: Present results appear to be promising to enlarge the population who can be offered semen cryopreservation in our laboratory, including Klinefelter patients, severe oligo- and criptozoospermic menand patients undergoing testicular biopsy. Trial registration number: not applicable